Cathode and preparation method thereof, light-emitting device and display device
By introducing a water-oxygen adsorption layer into the cathode of the QLED device, the problem of imbalance in hole and electron transport is solved, and the efficiency and stability of the device are improved.
Patent Information
- Application Number
- CN202311238038.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-02-18
AI Technical Summary
In a quantum dot light emitting diode (QLED) device, the number of holes and electrons transmitted to the light emitting layer are unbalanced, resulting in the quantum dot being charged and non-radiated luminescence such as Auger recombination occurs.
A cathode is designed, including a first conductive layer, a water-oxygen adsorption layer and a second conductive layer arranged in sequence. The water oxygen adsorption layer can adsorb water oxygen, causing the first conductive layer and the second conductive layer to be gradually partially oxidized, reducing electron injection and improving the device's current balance.
By improving the transmission balance between holes and electrons, the efficiency and stability of the light-emitting device are improved, and non-radiated luminescence phenomenon is reduced.
Smart Images

Figure CN119486481A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of display technology, and in particular to a cathode and a preparation method thereof, a light-emitting device, and a display device. Background Art
[0002] Organic light-emitting diodes (OLEDs) have the advantages of self-luminescence, high contrast, ultra-lightness, ultra-thinness and flexibility, and have become a display technology that has attracted much attention. Quantum dot light-emitting diode (QLED) devices have the advantages of saturated color of emitted light, adjustable wavelength and high quantum yield of light emission, and have become a strong competitor to OLED in recent years.
[0003] Typically, a QLED device includes an anode, a hole injection layer (HIL), a hole transport layer (HTL), a quantum dot light emitting layer, an electron transport layer (ETL), and a cathode. Figure 1 Schematic diagram of the transmission of holes and electrons in QLED devices. At present, in QLED devices with better performance, organic small molecules or polymers are generally used as hole transport layers, such as TPD, Poly-TPD, PVK, TFB, etc. The HOMO energy levels of these materials are between 5.2 and 5.8. Quantum dot materials generally adopt a core-shell structure, and the HOMO energy level is generally above 6.5. Especially for blue quantum dots, their HOMO energy level is deeper, resulting in a large energy level barrier that holes need to cross from the hole transport layer to the light-emitting layer. On the other hand, the electron transport layer generally uses inorganic nanoparticle oxides, such as ZnO, BaO, TiO2, etc., whose LUMO energy level is around 4, which is very close to the LUMO energy level of quantum dots. Therefore, the energy level barrier that electrons need to cross from the electron transport layer to the light-emitting layer is very small. In addition, the hole mobility of the hole transport layer is several orders of magnitude lower than the electron mobility of the electron transport layer. The above factors lead to an imbalance in the number of holes and electrons transferred to the light-emitting layer, which can cause the quantum dots to be charged and cause non-radiative luminescence such as Auger recombination. Summary of the invention
[0004] Based on this, it is necessary to provide a cathode and a preparation method thereof, a light-emitting device, and a display device to solve the problem of imbalance between the number of holes and the number of electrons transmitted to the light-emitting layer.
[0005] A cathode comprises a first conductive layer, a water and oxygen adsorption layer and a second conductive layer which are stacked in sequence;
[0006] The first conductive layer comprises a first metal and an oxide thereof, and the second conductive layer comprises a second metal and an oxide thereof.
[0007] In one embodiment, the material of the water oxygen adsorption layer includes at least one of polyacrylate, polyvinyl alcohol, polyoxyalkylene, polyurethane and acrylate.
[0008] In one embodiment, the polyacrylate includes sodium polyacrylate and ammonium polyacrylate.
[0009] In one embodiment, the polyoxyalkylene includes at least one of polyethylene oxide and polypropylene oxide.
[0010] In one embodiment, the acrylic acid ester includes at least one of methyl acrylate, ethyl acrylate, 2-methyl methacrylate and 2-ethyl methacrylate.
[0011] In one embodiment, the polyurethane includes at least one of polyethyl carbamate and polybutyl carbamate.
[0012] In one embodiment, the thickness of the water oxygen adsorption layer is 3nm to 10nm.
[0013] In one embodiment, the thickness of the first conductive layer is 5 nm to 15 nm.
[0014] In one embodiment, the second conductive layer has a thickness of 15 nm to 50 nm.
[0015] In one embodiment, the first metal and / or the second metal includes at least one of aluminum, magnesium, silver, platinum, palladium, gold, copper, nickel, zinc, tungsten, iron, nickel, chromium, and titanium.
[0016] In one embodiment, the first metal and the second metal are the same.
[0017] A method for preparing a cathode comprises the following steps:
[0018] preparing a first metal layer, and baking the first metal layer in an oxygen-containing atmosphere to obtain a first conductive layer;
[0019] preparing a water oxygen adsorption layer on the first conductive layer;
[0020] A second conductive layer is prepared on the water oxygen adsorption layer.
[0021] In one embodiment, the water oxygen adsorption layer is prepared by a solution method.
[0022] In one embodiment, the steps of preparing the water oxygen adsorption layer include:
[0023] In an oxygen-containing atmosphere, coating a solution containing a water and oxygen adsorbing material on the first conductive layer and drying the solution to form a film; and / or
[0024] The step of preparing the second conductive layer comprises:
[0025] A second metal layer is deposited on the water oxygen adsorption layer.
[0026] A light-emitting device comprises the cathode or the cathode prepared by the preparation method.
[0027] A display device comprises the light-emitting device.
[0028] Compared with the conventional solution, the cathode and its preparation method, the light emitting device and the display device have the following advantages:
[0029] Beneficial effects:
[0030] The above-mentioned cathode and preparation method thereof arrange a water oxygen adsorption layer between the first conductive layer and the second conductive layer. Since the water oxygen adsorption layer can adsorb water oxygen, the adsorbed water oxygen can gradually partially oxidize the first conductive layer and the second conductive layer. After the metal material is partially oxidized, its electron injection is weakened, thereby improving the electrical balance of the device and improving the efficiency and stability of the device.
[0031] The above-mentioned light-emitting device has the cathode of any of the above-mentioned embodiments, and the above-mentioned display device has the above-mentioned light-emitting device, thereby being able to obtain corresponding technical effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the transport of holes and electrons in QLED devices;
[0033] Figure 2 is a schematic structural diagram of a cathode according to an embodiment;
[0034] Figure 3 To include Figure 2 A schematic structural diagram of a light-emitting device with a cathode as shown;
[0035] Figure 4 1 is the JV characteristic curve of the electron-single carrier device corresponding to Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0036] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0037] It should be noted that when an element is referred to as being "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0038] In the description of the present invention, it should be understood that the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number or order of the indicated technical features.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0040] like Figure 2 As shown, the cathode 180 of one embodiment of the present invention includes a first conductive layer 181, a water oxygen adsorption layer 182 and a second conductive layer 183 stacked in sequence, the first conductive layer 181 includes a first metal and its oxide, and the second conductive layer 183 includes a second metal and its oxide.
[0041] The cathode 180 has a water oxygen adsorption layer 182 disposed between the first conductive layer 181 and the second conductive layer 183. Since the water oxygen adsorption layer 182 can adsorb water oxygen, the adsorbed water oxygen can gradually partially oxidize the first conductive layer 181 and the second conductive layer 183. After the metal material is partially oxidized, its electron injection is weakened, thereby improving the electrical balance of the device and improving the efficiency and stability of the device.
[0042] The water-oxygen adsorption layer 182 preferably has a relatively high surface energy. Preferably, the surface energy of the water-oxygen adsorption layer 182 is 100 mJ / m 2 More than, for example, 200 mJ / m 2 、300mJ / m 2 、400mJ / m 2 、500mJ / m 2 、600mJ / m 2Etc. Surface energy is due to the surface tension of the material surface, and the bond energy of the surface layer atoms toward the outside is not compensated, so that the surface particles have additional potential energy than the particles in the body. In this example, the water-oxygen adsorption layer 182 has a higher surface energy. The high surface energy means that the surface bond energy is very high, and it can adsorb water and oxygen to reduce the surface bond energy to stabilize.
[0043] The water-oxygen adsorption layer 182 preferably has a lower water contact angle. In one example, the water contact angle of the water-oxygen adsorption layer 182 is 10° to 80°. Further, the water contact angle of the water-oxygen adsorption layer 182 is 10° to 60°. Further, the water contact angle of the water-oxygen adsorption layer 182 is 10° to 30°. The water contact angle refers to the contact angle between the water-oxygen adsorption layer 182 and water. The smaller the water contact angle, the better the wettability of water to the surface of the water-oxygen adsorption layer 182. In this example, the water-oxygen adsorption layer 182 has a smaller water contact angle and can better adsorb water and oxygen.
[0044] Optionally, the material of the water oxygen adsorption layer 182 may be but is not limited to at least one of polyacrylate, polyvinyl alcohol, polyoxyalkylene, polyurethane and acrylate. The above materials have good water oxygen adsorption capabilities and can weaken the electron injection capability, thereby better improving the electrical balance of the device.
[0045] Among them, examples of polyacrylates include sodium polyacrylate, ammonium polyacrylate, etc. Examples of polyoxyalkylenes include polyethylene oxide, polypropylene oxide, etc. Examples of polyurethanes include polyethyl carbamate, polybutyl carbamate, etc. Examples of acrylates include methyl acrylate, ethyl acrylate, methyl 2-methacrylate, ethyl 2-methacrylate, etc.
[0046] In one example, the thickness of the water oxygen adsorption layer 182 is 3 nm to 10 nm, for example, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc.
[0047] Optionally, the first metal may be at least one of, but not limited to, aluminum, magnesium, silver, platinum, palladium, gold, copper, nickel, zinc, tungsten, iron, nickel, chromium, and titanium.
[0048] In one example, the thickness of the first conductive layer 181 is 5 nm to 15 nm, for example, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, etc.
[0049] Optionally, the second metal may be at least one of, but not limited to, aluminum, magnesium, silver, platinum, palladium, gold, copper, nickel, zinc, tungsten, iron, nickel, chromium, and titanium.
[0050] The first metal and the second metal may be the same or different.
[0051] In one example, the thickness of the second conductive layer 183 is greater than the thickness of the first conductive layer 181 .
[0052] In one example, the thickness of the second conductive layer 183 is 15 nm to 50 nm, for example, 15 nm, 18 nm, 21 nm, 24 nm, 27 nm, 30 nm, 33 nm, 36 nm, 39 nm, 42 nm, 45 nm, 48 nm, 50 nm, etc.
[0053] Furthermore, the present invention also provides a method for preparing the cathode of any of the above examples.
[0054] A method for preparing a cathode in one embodiment comprises the following steps:
[0055] Step S1, preparing a first metal layer, and baking the first metal layer in an oxygen-containing atmosphere to obtain a first conductive layer.
[0056] Step S2, preparing a water oxygen adsorption layer on the first conductive layer.
[0057] Step S3, preparing a second conductive layer on the water oxygen adsorption layer.
[0058] The preparation method of the above cathode is to prepare a water-oxygen adsorption layer on the first metal layer after preparing the first metal layer. Since the water-oxygen adsorption layer can absorb water oxygen, the absorbed water oxygen can cause the first metal layer to be continuously oxidized. A second conductive layer is prepared on the water-oxygen adsorption layer. The absorbed water oxygen can cause the second conductive layer to be gradually partially oxidized. After the metal material is partially oxidized, its electron injection is weakened, thereby improving the electrical balance of the device and improving the efficiency and stability of the device.
[0059] The first metal layer is baked in an oxygen-containing atmosphere, such as air. After the first metal layer is prepared, it is exposed to an oxygen-containing atmosphere to be oxidized, and baked to accelerate the oxidation process. Subsequently, a water-oxygen adsorption layer is prepared on the first metal layer, and the water-oxygen adsorption layer can keep the first metal layer continuously oxidized.
[0060] Optionally, the method for preparing the water oxygen adsorption layer is a solution method, such as spin coating, printing, inkjet printing, doctor blade coating, printing, dip-coating, immersion, spraying, roll coating, casting, slit coating, strip coating, etc. More specifically, the step of preparing the water oxygen adsorption layer includes: coating a solution containing a water oxygen adsorption material on the first conductive layer in an oxygen-containing atmosphere, and drying. The water oxygen adsorption material may be, but is not limited to, at least one of polyacrylate, polyvinyl alcohol, polyoxyalkylene, polyurethane, and acrylate.
[0061] In one example, step S3 includes depositing a second metal layer on the water oxygen adsorption layer.
[0062] The water oxygen adsorbed by the second metal layer can gradually partially oxidize the second metal layer. After the metal material is partially oxidized, its electron injection is weakened, thereby improving the electrical balance of the device and enhancing the efficiency and stability of the device.
[0063] Optionally, the first metal layer and the second metal layer may be prepared by, but is not limited to, evaporation.
[0064] Furthermore, the present invention also provides a light-emitting device, comprising the above-mentioned cathode or the cathode prepared by the above-mentioned preparation method.
[0065] like Figure 3 As shown, the light emitting device 100 of an embodiment includes an anode 120, a light emitting layer 150 and a cathode 180 of any one of the above examples. The light emitting layer 150 is disposed between the anode 120 and the cathode 180.
[0066] The above-mentioned light-emitting device has the above-mentioned cathode, thereby being able to obtain corresponding technical effects.
[0067] The material of the anode 120 may be selected from but not limited to one or more of a metal electrode, a carbon electrode, a doped or undoped metal oxide electrode and a composite electrode; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from at least one of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2. Here, “ / ” represents a stacked structure. For example, the composite electrode AZO / Ag / AZO represents an electrode with a composite structure of three stacked layers consisting of an AZO layer, an Ag layer and an AZO layer.
[0068] The material of the light-emitting layer 150 is selected from at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, Cd At least one of ZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbS Se, SnPbSeTe and SnPbSTe, the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaIn At least one of GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the core-shell structured quantum dots includes any one of the above-mentioned single-structured quantum dots, and the shell material of the core-shell structured quantum dots includes CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and at least one of the above-mentioned single-structured quantum dots.
[0069] It is understandable that the quantum dot light-emitting material may also be combined with an organic ligand, which may be selected from but not limited to at least one of OA (oleic acid), OAM (oleylamine), and TOP (trioctyl phosphine).
[0070] It is understood that a carrier functional layer may be provided between the cathode 180 and the light emitting layer 150 and / or between the light emitting layer 150 and the anode 120. The carrier functional layer may be, for example, one or more of a hole injection layer, a hole transport layer, an electron transport layer and an electron injection layer.
[0071] Figure 3 The light emitting device 100 includes a substrate 110, an anode 120, a hole injection layer 130, a hole transport layer 140, a light emitting layer 150, an electron transport layer 160, an electron injection layer 170 and a cathode 180 which are stacked in sequence.
[0072] The substrate 110 includes a substrate and a TFT driving array disposed on the substrate. The substrate may be a rigid substrate, such as a glass substrate, preferably a silicon-based substrate with good thermal conductivity, or a flexible substrate, such as a PI (polyimide) substrate.
[0073] The material of the hole injection layer 130 is a material with hole injection capability, selected from one or more of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), a PEDOT:PSS / PFI mixture, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane (F4-TCNQ), 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HATCN), copper phthalocyanine (CuPc), transition metal oxides, and transition metal sulfur compounds; wherein the transition metal oxides include one or more of NiO, MoO2, WO3, and CuO; and the metal sulfur compounds include one or more of MoS2, MoSe2, WS3, WSe3, and CuS.
[0074] The material of the hole transport layer 140 is a material having hole injection capability, selected from poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine) (TFB), polyvinylcarbazole (PVK), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (poly-TPD), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine) (PFB), 4,4',4"-tri(carbazole-9-yl)triphenylamine (TCATA), 4,4'-bis(9-carbazole)biphenyl (CBP), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD), N,N'-diphenyl-N,N'-(1-naphthyl)-1 ,1'-biphenyl-4,4'-diamine (NPB), poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane (F4-TCNQ), 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HATCN), copper phthalocyanine (CuPc), Spiro-NPB, Spiro-TPD, doped graphene, undoped graphene, C60, P-type gallium nitride, doped or undoped NiO, V2O5, CrO3, CuO, CuS, MoO3, MoS2, MoSe2, WO3, WS2, WSe2 and CuSCN, etc. One or more.
[0075] In some of the examples, the material of the hole transport layer 140 is PVK. Compared with the other small molecules mentioned above, PVK has the advantage of good film-forming property and is more suitable for spin coating.
[0076] The material of the electron transport layer 160 is a material known in the art for an electron transport layer. For example, it can be selected from one or more of doped or undoped inorganic nanocrystals and organic materials; wherein the undoped inorganic nanocrystals are selected from ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, Fe2O3, CrO3, WO3, CdO, CuO, MoO2, ZnS, ZnSe, CdS, InP, GaP, SnO2, WO3, Ta2O3, HfO3, ZrSiO4, BaTiO3, BaZrO3, Si3N 4; the doped inorganic nanocrystals include the undoped inorganic nanocrystals and doping elements, and the doping elements are selected from one or more of Mg, Ca, Li, Ga, Al, Co, In, Mn, Cd, Cs or Cu; the organic material is selected from one or more of polymethyl methacrylate, polyvinyl butyral, oxazole compounds, isoxazole compounds, triazole compounds, isothiazole compounds, oxadiazole compounds, thiadiazole compounds, perylene compounds or aluminum complexes.
[0077] The material of the electron injection layer 170 may be, but is not limited to, at least one of LiF, NaF, and CsF. The above halides can form a double electrode with a metal cathode, thereby reducing the barrier of electron injection and improving the luminous efficiency.
[0078] Furthermore, the present invention also provides a display device, comprising a plurality of the light-emitting devices 100 arranged in an arranged manner.
[0079] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.
[0080] The following specific examples are provided to further illustrate the present invention.
[0081] Example 1
[0082] This embodiment provides a light emitting device and a method for manufacturing the same.
[0083] The method for preparing a light emitting device comprises the following steps:
[0084] Step 1, providing a glass substrate, preparing an anode on the glass substrate, and the material of the anode is ITO.
[0085] Step 2: Spin-coat the conductive polymer PEDOT:PSS ink on the anode, dry it to form a film, and then anneal it at 150° C. for 15 minutes to obtain a hole injection layer with a thickness of 45 nm.
[0086] Step 3: Spin-coat the TFB ink on the hole injection layer, dry it to form a film, and then anneal it at 230° C. for 30 minutes to obtain a hole transport layer with a thickness of 30 nm.
[0087] Step 4: Spin-coat quantum dot ink on the hole transport layer, the quantum dots are CdZnSe / ZnSe / ZnS quantum dots, and have an organic ligand OA (oleic acid). After drying to form a film, anneal at 100° C. for 10 minutes to obtain a light-emitting layer with a thickness of 15 nm.
[0088] Step 5: spin-coat ZnO ink on the light-emitting layer, dry in vacuum to form a film, and then anneal at 80° C. for 15 minutes to obtain an electron transport layer with a thickness of 30 nm.
[0089] Step 6, evaporating metal Ag on the electron transport layer, exposing it to air after evaporation, and baking it in air atmosphere at 100° C. for 30 minutes to obtain a first metal layer with a thickness of 10 nm.
[0090] Step 7, in an air atmosphere, spin-coat ethyl acrylate on the first metal layer, and then bake in an air atmosphere at 80° C. for 10 minutes to obtain a 5 nm water oxygen adsorption layer.
[0091] Step 8: evaporate metal Ag on the water oxygen adsorption layer to obtain a second metal layer with a thickness of 20 nm.
[0092] Step 9, preparing a light extraction layer on the second metal layer and encapsulating it to obtain a light emitting device.
[0093] Example 2
[0094] The method for preparing the light emitting device provided in this embodiment is substantially the same as that in Embodiment 1, except that the material of the water and oxygen adsorption layer is ammonium polyacrylate.
[0095] Example 3
[0096] The method for preparing the light-emitting device provided in this embodiment is substantially the same as that in Embodiment 1, except that the material of the water oxygen adsorption layer is polyvinyl alcohol.
[0097] Example 4
[0098] The method for preparing the light emitting device provided in this embodiment is substantially the same as that in Embodiment 1, except that the material of the water oxygen adsorption layer is polyethylene oxide.
[0099] Example 5
[0100] The method for preparing the light emitting device provided in this embodiment is substantially the same as that in Embodiment 1, except that the material of the water and oxygen adsorption layer is polyurethane.
[0101] Example 6
[0102] The method for preparing the light-emitting device provided in this embodiment is substantially the same as that in Embodiment 1, except that the material of the first cathode layer is Mg.
[0103] Comparative Example 1
[0104] The difference between this comparative example and Example 1 is that in step 6, metal Ag is evaporated on the electron transport layer to obtain a cathode with a thickness of 35 nm, and then a light extraction layer is directly prepared on the cathode, and encapsulated to obtain a light-emitting device. In addition, the above preparation processes of the comparative example are all carried out in a nitrogen glove box.
[0105] The light emitting devices prepared in the above-mentioned Examples 1 to 6 and Comparative Example 1 were subjected to performance tests, including tests on external quantum efficiency, current efficiency and lifespan, and the results are shown in Table 1.
[0106] Table 1 Light emitting device performance test results
[0107]
[0108] It can be seen from the test results in Table 1 that the external quantum efficiency, current efficiency and lifespan of the light-emitting devices prepared in Examples 1 to 6 are significantly improved compared with those in Comparative Example 1.
[0109] In order to verify the electron injection effect of Example 1 and Comparative Example 1, corresponding electron-single carrier devices were prepared. The device structure was ITO / BQD / ZnO / cathode in Example 1 or cathode in Comparative Example 1. The JV characteristic curves obtained by the test were as follows: Figure 4 As shown. Figure 4 It can be seen that the electron injection in Example 1 is significantly weakened relative to that in Comparative Example 1.
[0110] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0111] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A cathode, characterized in that: It comprises a first conductive layer, a water oxygen adsorption layer and a second conductive layer which are stacked in sequence; The first conductive layer comprises a first metal and an oxide thereof, and the second conductive layer comprises a second metal and an oxide thereof.
2. The cathode according to claim 1, characterized in that The material of the water oxygen adsorption layer includes at least one of polyacrylate, polyvinyl alcohol, polyoxyalkylene, polyurethane and acrylate.
3. The cathode according to claim 2, characterized in that The polyacrylate includes sodium polyacrylate and ammonium polyacrylate; and / or, The polyoxyalkylene includes at least one of polyethylene oxide and polypropylene oxide; and / or, The acrylic acid ester includes at least one of methyl acrylate, ethyl acrylate, 2-methyl methacrylate and 2-ethyl methacrylate; and / or, The polyurethane includes at least one of polyethyl carbamate and polybutyl carbamate.
4. The cathode according to any one of claims 1 to 3, characterized in that The thickness of the water oxygen adsorption layer is 3nm to 10nm; And / or, the thickness of the first conductive layer is 5nm to 15nm; And / or, the second conductive layer has a thickness of 15 nm to 50 nm.
5. The cathode according to any one of claims 1 to 3, characterized in that The first metal and / or the second metal include aluminum, magnesium, silver, platinum, palladium, gold, copper, nickel, zinc, 、 At least one of tungsten, iron, nickel, chromium and titanium; And / or, the first metal and the second metal are the same.
6. A method for preparing a cathode, characterized in that: The following steps are involved: preparing a first metal layer, and baking the first metal layer in an oxygen-containing atmosphere to obtain a first conductive layer; preparing a water oxygen adsorption layer on the first conductive layer; A second conductive layer is prepared on the water oxygen adsorption layer.
7. The preparation method according to claim 6, characterized in that: The water oxygen adsorption layer is prepared by a solution method.
8. The preparation method according to claim 7, characterized in that: The steps of preparing the water oxygen adsorption layer include: In an oxygen-containing atmosphere, coating a solution containing a water and oxygen adsorbing material on the first conductive layer and drying the solution to form a film; and / or The step of preparing the second conductive layer comprises: A second metal layer is deposited on the water oxygen adsorption layer.
9. A light emitting device, characterized in that: The invention comprises the cathode according to any one of claims 1 to 5 or the cathode prepared by the preparation method according to any one of claims 6 to 8.
10. A display device, characterized in that: The light emitting device comprising claim 9.